The Maternal Genetic Lineages of Ashkenazic Jews - Brook, Kevin Alan (Academic Studies Press, 2022)
This book presents up-to-date information on the origins of the Ashkenazic Jewish people from central and eastern Europe based on genetic research on modern and pre-modern populations. It focuses on the 129 maternal haplogroups that the author confirmed that Ashkenazim have acquired from distinct female ancestors who were indigenous to diverse lands that include Israel, Italy, Poland, Germany, North Africa, and China, revealing both their Israelite inheritance and the lasting legacy of conversions to Judaism. Genetic connections between Ashkenazic Jews and other Jewish populations, including Turkish Jews, Moroccan Jews, Tunisian Jews, Iranian Jews, and Cochin Jews, are indicated wherever they are known